The reality of distributed leadership practice among middle school principals in Makkah Al-Mukarramah from the female teachers’ point of view - Al-Lehyani, Ghada Mohammed; Al-Ghaidi, Aishah Hamd (Journal of Educational and Psychological Sciences, 2025)
The current study aimed at revealing the degree of leadership practice distributed in its overall dimensions to "Vision, Message, Objectives, Shared Responsibility, School Culture and Leadership Practices" among middle school principals in Makkah from the point of view of female teachers. As well as identifying the impact of of variables related to (years of experience, educational qualification) on teachers' assessment of the degree to which principals exercise distributed leadership. The study relied on the descriptive survey approach, and the questionnaire was used as a data collection, it consists of 31 phrase divided into four sub -dimensions.The school community included female teachers in middle schools in Makkah, from which a simple random sample of 339 female teachers was selected, out of a total of 2427 female teachers. After reviewing the core issues the results of the study concluded that the degree of practice of leadership distributed among school principals in Makkah came in a large degree with an average arithmetic 4.20.The school's cultural dimension came first rank in terms of degree of practice, then after shared responsibility, then after vision, the message and goals, and after leadership practices in the last rank.The study stated that there are no statistically significant differences in the practice of leadership distributed by middle school principals in Makkah from the teacher's point of view due to the different academic qualifications and number of years of experience. In contrast, there are differences in the dimension of vision, the message and goals attributable to experience towards female teachers with 10 years' experience and more.
Keywords: Distributed leadership; middle schools; school principals